Indonesia defence diplomacy strategy in resolving china claims to Indonesia exclusive economic zone in north natuna sea - SUMARLAN, SUTRIMO; SUDIBJO,; DOHAMID, AHMAD G. (The journal of contemporary issues in business and government, 2021)
China's unilateral claim through the nine-dash line map covered part of the Indonesian Exclusive Economic Zone in the North Natuna Sea. This research endeavored to explain Indonesian Defense Diplomacy Strategy in resolving the claim peacefully, by avoiding open military confrontation adhering to the principles of international maritime law UNCLOS 1982. The cooperation between the two countries is much broader and takes into account Indonesia's national interests. Therefore, the researchers offered an approach to avoid conflict through a defense diplomacy strategy that chose to cool down the tensions between the two countries. It was called as cool defense diplomacy.